2015
DOI: 10.1111/pde.12622
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic Trichoepithelioma: An Infrequent Entity not to be Missed: Report of Two Cases

Abstract: Desmoplastic trichoepitheliomas are rare benign tumors with follicular differentiation. They have rarely been described in children. We report two children with this uncommon condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In our review of the literature we found six other cases of pediatric DTs. There have been more recent reports of solitary DTs in children , as well as familial solitary DTs , but no solitary neonatal DT.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature we found six other cases of pediatric DTs. There have been more recent reports of solitary DTs in children , as well as familial solitary DTs , but no solitary neonatal DT.…”
Section: Discussionmentioning
confidence: 99%